Impact of Information Technology (IT) On Management Accounting and Financial Accounting - KHARE, DR. VIVEK (The journal of contemporary issues in business and government, 2021)
In this research, the theorizing and conceptualizing the recent confluent of management accounting & financial accounting with advances in the information technology) & explaining not only how this confluent is manifested in the technical & technological domain, but somehow it is reflected in their behavioral & organizational level convergence. In this paper attempts to clarify the impacts of IT on the accounting systems. The largest impact IT has on the accounting is companies' able to develop & use to computerized the systems to track & record financial transactions. The IT networks & database system reduced the period of a time that will accountants had to plan & deliver to the financial reports to management. In this program helps companies to rapidly, efficiently generate particular reports for the decision taking in the management. Other computerized accounting systems capabilities are: Increased functionality, faster processing, improved accuracy, & improved external reporting. So in, this paper highlights the advantages & inconveniences of the using IT in consider and reporting systems.